ANALISIS PERILAKU KONSUMEN BUAH DI PASAR TRADISIONAL DAN PASAR MODERN KECAMATAN KALIWATES, KABUPATEN JEMBER - Nyra Dewi Kartika; Evita Soliha Hani; Rudi Hartadi (University of Jember, 2010)
The phenomena of modern markets make consumers have many choices of buying fruits. However, this does not reduce interest of other consumers to choose traditional market as a choice of place to buy fruits. This research is intended to identify factors that influence fruit buying in traditional market and modern market as well as the type of buying behavior in District of Kaliwates, Jember Regency. Samples were taken by using Convenience Sampling. Research data used were primary and secondary data. Data was analyzed using factorial analysis and tested by involvement inventory. The research findings showed that (1) Factors that influenced fruits buying in traditional market were location and income, motivation, fruits physical performance and price, kinds of fruits, information and fund availability, number of fruits purchased, aroma. Meanwhile, factors that influenced fruit purchase in Modern Market, were price, information, selling, location, physical performance of fruits, motivation of buying, consumers’ interests; (2) Type of fruit buying behavior in Traditional Market and Modern Market were dissonance reducing buying behavior (3) The most frequently bought fruits in “Tanjung” Traditional Market were oranges, and those in Modern Market “Matahari” Supermarket were apples.Key Words: consumers behaviors, fruit, traditional market, modern market